IMPACT ASSESSMENT OF ICDS FOOD FORTIFICATION IN THE STATE OF UTTAR-PRADESH - Yadav, Ram Janak; Pandey, Arvind; Nigam, Arun Kumar; Singh, Padam; Gulati, Deepti (Indian Journal of Community Health, 2013)
Background and Objective: The concept of food fortification is relatively uncommon in India. Hence, sometimes due to ignorance or due to paucity of research to assess the impact of fortifying supplementary food in large feeding programmes, there is an apprehension that fortification may either lead to imbalance of nutrients in the body or may not really improve the nutritional status of people consuming marginal diets. This has lead to a prudent approach in taking bold decisions to fortify the ICDS supplementary food to reduce micronutrient malnutrition in different states. The current research planned to provide empirical evidence on the impact of fortified ICDS supplementary food through a well-conducted community based research study among the children between 12-59 months under programmatic conditions in state of Uttar Pradesh. Methods: The sampling design adopted was quasi experimental design under programme conditions. The study was taken up in Kanpur dehat district of UP. The block where fortified food was to be initiated constituted the experimental universe where as those blocks where fortified food was not to be initiated form the control universe. One block namely Maitha was taken as Experimental block and Rajpur as Control block. The base line was done in both the blocks. However, no intervention with fortified food could take place in Maitha and hence substituted by neighboring block Rasulabad. This block was named as benchmark block. Later after six months; benchmark survey was done in Rasulabad block. An end line survey was done after one year of intervention in all three blocks. At the base line, care was taken that experimental block and control block match in terms of socio economic and demographic parameters. Later, while substituting Maitha by Rasulabad at bench mark stage, it was assured that these two blocks matched in terms of socio economic and demographic parameters.The sample size worked out as 750 which were selected in the form of 30 villages and 25 children per village. 30 villages from each of these blocks were selected by Probability Proportion to population Size (PPS). From the each selected village, 25 children were selected for the anthropometrics measurement and dietary intake, 10 children for clinical examinations and 5 for the bio-chemical examinations. The sample design as well as the sample selection for endline assessment as well as for bench mark assessment was similar to those as was used in the baseline assessment. Results and Discussion: The majority of the children surveyed in these blocks belonged to lower socio-economic groups and the underprivileged sections of the society. There were considerable improvements in anemia in all these blocks. There is significant improvement in serum retinol levels of children at the end line stage in both the blocks. It is observed that there is significant improvement in Serum levels of children at the benchmark stage. Prevalence of severe malnutrition declined considerably in Maitha and Rajpur though it remained almost static in Rasulabad, giving further support to earlier observations on anemia. Only few (about 15%) children were taking home supplementary food and rest beneficiaries were consuming food at the AWCs. The paper show significant decline in the levels of anemia, vitamin A deficiency and malnutrition levels, an attempt was made to correlate these with the extent of food consumed. Interpretation and Conclusion: The findings reveal that fortified panjiri has been effective in improving anemia, serum retinol and nutritional status. It is also revealed that short duration of intervention is as effective as prolonged interventions. There are other studies also indicating that fortification of foods with iron has produced improvements in iron status. In India, where double fortification of salt, with iodine and iron, has the potential to prevent both iron and iodine deficiencies and has been effective for improved hemoglobin concentrations.